2004
DOI: 10.1097/01.wnr.0000127459.31232.c4
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in beat perception and dyslexia: evidence from French

Abstract: Recent research has suggested a novel link between deficits in the perception of cues relevant to speech rhythm (i.e., deficits in amplitude envelope rise time processing, or beat perception) and the phonological deficits seen in most dyslexic children. In this research, we investigated whether these beat perception deficits were specific to a stress-timed language, such as English, or whether they would generalize to languages with different rhythmic properties, such as French. Eighteen dyslexics, 18 reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
1
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 23 publications
9
91
1
8
Order By: Relevance
“…On the basis of prior behavioural work (Goswami et al, 2002(Goswami et al, , 2010bHämäläinen et al, 2009;Muneaux et al, 2004;Richardson et al, 2004;Surányi et al, 2009), we expected group effects to be strongest for rise time, however this was not the case. Rather, the most conservative explanation of the ERPs is that children with dyslexia have general differences in auditory neural processing in comparison to children of the same age who do not have dyslexia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of prior behavioural work (Goswami et al, 2002(Goswami et al, , 2010bHämäläinen et al, 2009;Muneaux et al, 2004;Richardson et al, 2004;Surányi et al, 2009), we expected group effects to be strongest for rise time, however this was not the case. Rather, the most conservative explanation of the ERPs is that children with dyslexia have general differences in auditory neural processing in comparison to children of the same age who do not have dyslexia.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility that has been widely investigated at the sensory level is that children with dyslexia have auditory processing difficulties (e.g., Tallal, 1980;Witton et al, 1998;Goswami et al, 2002). One auditory sensory deficit that is found in children with dyslexia across languages is inefficient processing of the rate of change of amplitude envelopes (also called rise time; Goswami et al, 2002Goswami et al, , 2010aHämäläinen et al, 2009;Muneaux et al, 2004;Richardson et al, 2004;Surányi et al, 2009). Here, we extend the investigation of rise time processing in dyslexia to the neural level by using EEG.…”
Section: Introductionmentioning
confidence: 99%
“…A new set of hypotheses has been put forward to link this deficit to speech processing and phonological development, ultimately aiming to account for poor reading and spelling skills. Goswami and colleagues [18][19][20][21][22][23] have documented group differences between children and adults diagnosed with dyslexia and control groups of typical readers (see Thomson & Goswami [24] for more references). The differences concern the ability to discriminate and categorize amplitudemodulated sounds that differ in the abruptness of the amplitude increase, termed 'rise time'.…”
Section: (B) Temporal Sampling Frameworkmentioning
confidence: 99%
“…Also, a number of studies have shown that auditory deficits are not restricted to rapid auditory processing (20). To the contrary, many ''slow'' tasks, such as 4-Hz amplitude modulation or 2-Hz frequency modulation detection, seem to be difficult for children with developmental language learning disorders (21)(22)(23)(24)(25). Given that speech intelligibility depends heavily on the integrity of its low-frequency amplitude modulations (e.g., ref 26), a slow temporal-processing deficit might offer a viable explanation of speech perception deficits in SLI.…”
mentioning
confidence: 99%